Pengaruh Komitmen Organisasi, Kemampuan Teknik Personal dan Sistem Pengendalian Internal Terhadap Efektivitas Sistem Informasi Akuntansi - Ni Made Ayu Kumala; Ni Komang Sumadi (Hita Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of organizational commitment, personal technical ability and internal control system on the effectiveness of accounting information systems at LPDs in Blahbatuh District. This research was conducted in all LPDs in Blahbatuh District. The number of samples used were 164 LPD employees from a population of 259 LPD employees, using purposive random sampling technique. Data was collected through a questionnaire. The analysis technique used is multiple linear regression. The results of hypothesis testing indicate that organizational commitment, personal technical ability, and internal control systems have a positive and significant effect on the effectiveness of the accounting information system at the LPD in Blahbatuh District.